Um estudo sobre a aplicação das normas internacionais de contabilidade na prestação dos serviços pelos escritórios contábeis no município de São Paulo - Santos, Daniel Rodrigo de Sousa (2017)
There are 8,687 accounting organizations in São Paulo city, which account for 14.27% of the Brazilian accounting offices. The accounting services offered by these companies are focused on meeting the accounting demands of micro and small enterprises, being that, as time goes by, they have also dedicated themselves to the provision of accounting services in the fulfillment of fiscal demands. However, since the creation of the Public Bookkeeping System (Sistema Público de Escrituração – Sped), the tax office has been modernizing itself and harmonizing the fiscal practices to the current accounting standards, therefore, accounting organizations must comply with accounting standards and, consequently, meet tax demands. Thus, this paper aims at highlighting the use of the new accounting standards in the provision of accounting service by the accounting offices which are located in São Paulo city, because, since the enactment of Law 11.638 / 07, that is, ten years ago, Brazil has initiated the process of harmonizing Brazilian accounting standards with international standards. To achieve such goal, a questionnaire containing open and closed questions regarding both the size of the companies served by the accounting offices and the standards to be applied to micro and small enterprises was prepared and sent to accounting professionals through stakehoulders, e-mails and social networks. Therefore, this study is based upon non-experimental data and on a descriptive transversal study, whose data collection was performed in a single moment. As conclusion, from the analysis of the answers in the questionnaires, it is possible to verify that accounting organizations currently do not comply with accounting standards and continue to link the provision of accounting services only to tax demands